Effectiveness of Paradoxical Treatment Model on Emotional Regulation and Perception of Rejection in Retirees - Ebrahimpour Khortoomi, Fatemeh; Khedmatgozar, Hossein (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Retirement is one of the most sensitive situations in the life of any working individual, requiring numerous skills for optimal adaptation. Among these skills is the ability to regulate emotional behavior. The present study aimed to determine the effectiveness of the paradoxical treatment model on emotional regulation and the perception of rejection among retirees of Mellat Bank in Tehran. Methods and Materials: The research method was quasi-experimental, utilizing a pre-test-post-test design with a control group. The population consisted of all male and female retirees of Mellat Bank in Tehran in the year 2023, and based on a convenience sampling method, 30 individuals were selected and randomly assigned to experimental (15 participants) and control (15 participants) groups. The instruments for data collection included the Kraaij and Garnefski (2019) Emotional Regulation Questionnaire and the Leary and MacDonald (2010) Rejection Sensitivity Questionnaire. The paradoxical therapy approach sessions consisted of six 60-minute sessions, with the experimental group members attending weekly sessions. For data analysis, multivariate and univariate covariance analyses were employed using SPSS version 22. Findings: The results indicated that the paradoxical treatment model was effective in improving emotional regulation and perception of rejection among the retirees. Conclusion: It can be concluded that the implementation of the paradoxical therapy approach has led to an improvement in emotional regulation and a decrease in rejection perception scores.